THE INTERSECTION OF ISLAM AND POLITICS IN INDONESIA'S LOCAL AUTONOMY ERA - Mukrimin, Mukrimin (Al-Ijtima`i: International Journal of Government and Social Science, 2023)
The article examines the impact of local governance on Islam and politics in Indonesia, examining how decentralization of power has allowed local politicians to collaborate with Islamic organizations and parties to affect local policy. Local officials have been accused of Islamization, which entails promoting Islamic ideals and practices through governmental policy. The article examines the issue of mixing religion and politics, stressing that some Indonesians feel Islam should be crucial in the country's political landscape. In contrast, others believe religion and politics should be kept separate. After reviewing the many perspectives on Islam and politics in Indonesia, the article finishes by underlining the need for a more harmonious interaction between these two sectors. It emphasizes the existence of inter-religious conflicts in Indonesia, some of which have been fuelled by politicians' exploitation of sectarianism to further their interests. As a result, the paper suggests that politicians and policymakers adopt a more inclusive approach that respects religious diversity and encourages communication among different religious groups. This essay proposes that education and the media can promote inter-religious harmony and tolerance, resulting in a more peaceful and prosperous society.